Gendered local politics: the barriers to women's representation in Turkey. Issue 4 (18th May 2020) - Sumbas, Ahu
ABSTRACT: Starting out from the argument that the political experience of women diverges at different levels of politics, this article aims to provide an understanding of the challenges faced by female mayors in local politics in Turkey. Nation-wide empirical data was gathered through in-depth interviews with 34 female mayors who were elected to office for the 2004–2009 and 2009–2014 terms. The framework analysis of the data reveals that the challenges in question stem from the cultural factors that reinforce the gendered local politics in Turkey. These barriers are embodied in the male-dominance of political seats, the hegemony of masculine discourse over political language, and the burden of traditional gendered roles on female mayors. The presence and authority of female mayors has come to be seen as a threat to existing political interests, with political language serving to devalue women, and to subordinate their demands to the agendas set by the male-dominated elite. The gendered responsibilities in the home have come to be associated with the political achievements of female mayors in Turkey, bolstering the gender bias in local politics, and thus preventing the elimination of distributive injustice and political inequality in democratic practice in Turkey regarding women's identity and interests.